Prescribing for different antibiotic classes across age groups in the Kaiser Permanente Northern California population in association with influenza incidence, 2010–2018. (26th October 2022) - Goldstein, Edward; Fireman, Bruce H.; Klein, Nicola P.; Lipsitch, Marc; Ray, G. Thomas
Abstract: There is limited information on the volume of antibiotic prescribing that is influenza-associated, resulting from influenza infections and their complications (such as streptococcal pharyngitis). We estimated that for the Kaiser Permanente Northern California population during 2010–2018, 3.4% (2.8%–4%) of all macrolide prescriptions (fills), 2.7% (2.3%–3.2%) of all aminopenicillin prescriptions, 3.1% (2.4%–3.9%) of all 3rd generation cephalosporins prescriptions, 2.2% (1.8%–2.6%) of all protected aminopenicillin prescriptions and 1.3% (1%–1.6%) of all quinolone prescriptions were influenza-associated. The corresponding proportions were higher for select age groups, e.g. 4.3% of macrolide prescribing in ages over 50 years, 5.1% (3.3%–6.8%) of aminopenicillin prescribing in ages 5–17 years and 3.3% (1.9%–4.6%) in ages <5 years was influenza-associated. The relative contribution of influenza to antibiotic prescribing for respiratory diagnoses without a bacterial indication in ages over 5 years was higher than the corresponding relative contribution to prescribing for all diagnoses. Our results suggest a modest benefit of increasing influenza vaccination coverage for reducing prescribing for the five studied antibiotic classes, particularly for macrolides in ages over 50 years and aminopenicillins in ages <18 years, and the potential benefit of other measures to reduce unnecessary antibiotic prescribing for respiratory diagnoses with no bacterial indication, both of which may contribute to the mitigation of antimicrobial resistance.